SMALL MODULAR NUCLEAR REACTORS - NEW PERSPECTIVES IN ENERGY TRANSITION (Balkan Journal of Applied Mathematics and Informatics, 2022)
Nuclear power has been declining in importance over the last quarter century, with its share of global electrical energy generation decreasing from 17.5% in 1996 to around 10% in 2019, mostly over gas-fired power plants and recently renewable energy sources. Small modular and advanced nuclear reactors (SMR) have been proposed as potential way of dealing with the problem, such as specifically economic competitiveness, risk of accidents, link to proliferation and production of waste, confronting nuclear power technology.This perspective paper examines whether these new designs can indeed solve these problems, with a particular focus on the economic and global climate challenges. It briefly discusses the technical challenges confronting advanced reactor designs and the many decades it might take for these to be commercialized, if ever, as a result of slow-paced development of appropriate legislative. Next, it examines the potential savings from their light and modular construction, and explains why the historical record suggests that these savings could be adequate to compensate for the economic challenges resulting from the lower generation capacity. It then critically examines arguments offered by advocates of these technologies to justify subsidizing and constructing these kinds of nuclear plants with respect to job creation and other potential uses of electricity generated in combination with heat providing balancing mechanism for emerging installation of renewable energy sources It concludes with an assessment of the markets for these technologies in the coming decade.
Keywords: Nuclear power, Nuclear reactors, Small modular reactors, Renewables, Energy generation